Koordinasi Penanganan dan Pencegahan Stunting Melalui Efektivitas Implementasi Program di Cibinong Cianjur - Nugraha, Anggi; Dewi, Ni Putu Juwanita (PT. Alahyan Publisher Sukabumi, 2025)
The analysis results indicate that all hypotheses possess strong significance levels. Coordination is proven to have a positive and highly dominant influence on the effectiveness of program implementation, with a path coefficient of 0.967 and a T-statistic value of 181.520. Directly, coordination also contributes to stunting reduction with a coefficient of 0.582 (T-statistics 7.557). The effectiveness of program implementation is proven to serve as a significant mediating variable, with an indirect effect coefficient of 0.387 (T-statistics 5.188). The coefficient of determination (R2) shows that this model is capable of explaining 95.0% of the variance in stunting reduction, while the predictive relevance value (Q2) of 0.643 indicates a very strong model predictive capability. In conclusion, strengthening cross-sectoral coordination accompanied by effective program execution is a strategic key in accelerating sustainable stunting reduction at the local level.